Dual‐band GaN power amplifiers with novel DC biasing networks incorporating offset double‐sided parallel strip line. Issue 3 (1st February 2016) - Gu, Liming; Che, Wenquan; Chen, Shichang; Cai, Qi; Zhang, Mi; Xue, Quan
Abstract : This study presents a novel dual‐band DC biasing network and its application in the design of GaN power amplifiers (PAs). By integrating offset double‐sided parallel strip line which can easily realise high characteristic impedance and thus narrow microstrip line, the proposed biasing network can obtain much higher operation frequency ratio than the conventional design. To demonstrate the new methodology, two dual‐band GaN PAs applying the presented dual‐band DC biasing network are implemented. The operation frequencies are 1.8/3.5 and 0.9/3.5 GHz. Three‐section networks for complex load are used for dual‐frequency input and output matching. Good agreement between the simulation and measurement is observed, which fully demonstrate the feasibility and validity of the presented DC bias networks in power amplifier designs.